Improved methods for evaluating pre‐clinical and histological effects of subcutaneous fat reduction using high‐intensity focused ultrasound in a porcine model. Issue 2 (11th August 2016) - Kwon, T.‐R.; Im, S.; Jang, Y.‐J.; Oh, C. T.; Choi, E. J.; Jung, S. J.; Hong, H.; Choi, Y. S.; Choi, S. Y.; Kim, Y. S.; Kim, B. J.
Abstract : Background: Non‐invasive body sculpting procedures are becoming increasingly popular. High‐intensity focused ultrasound (HIFU) treatment is a non‐surgical fat reduction procedure that permanently destroys unwanted abdominal fat. Despite its increasing popularity, evaluation methods for the procedure have not yet been fully developed. Aims: The objective of this study was to develop evaluation methods for HIFU for non‐surgical, permanent fat reduction in the anterior abdomen using a porcine model. Methods: The abdomens of female pigs ( Sus scrofa, n = 7) were treated with a HIFU device (SCIZER ™, Classys Inc, Seoul, Korea). We examined treatment effects using photography, ultrasound, gross and microscopic pathology, and serum lipid and liver function level analysis, carbon tracer test, and histological examination in order to determine the mechanism of action, efficacy, and safety of the procedure. Results: HIFU treatment effectively reduced abdominal fat in a porcine model; it accurately treated the target subcutaneous fat layer and the subcutaneous fat was reduced effectively via ultrasonic measurement after HIFU treatment. On histological staining (H&E, toluidine blue, oil red O and immunohistochemistry), we found that subcutaneous fat reduction occurred effectively via accurate treatment of the targeted subcutaneous fat layer. On hematological assay, there were changes within normal range, and values remained stable after 48 h. Via carbon tracer test, the migration of activated macrophages was identified within the axillary lymph node (LN). PPAR‐delta, a protein defined by immunohistochemistry staining, was overexpressed in the early stage on days 1 and 7, but a gradual decreasing pattern was confirmed. Conclusion: We successfully used a HIFU device for body contouring and fat reduction in a pre‐clinical study. These results provide that the essential clues toward the effective evaluation, guiding selection of the appropriate diagnostic investigations.